2022
DOI: 10.1111/mve.12604
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observation to assess dengue risk due toAedes aegyptiandAedes albopictusin a subtropical city of Argentina

Abstract: Earth observation environmental features measured through remote sensing and models of vector mosquitoes species Aedes aegypti and Ae. albopictus provide an advancement with regards to dengue risk in urban environments of subtropical areas of Argentina. The authors aim to estimate the effect of landscape coverage and spectral indices (Normalized Difference Vegetation Index [NDVI], Normalized Difference Water Index [NDWI] and Normalized Difference Built-up Index [NDBI]) on the larvae abundance of Ae. aegypti an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…aegypti was prevailed over Ae. albopictus in this urban area and was associated with places with moderate construction activity (Martín et al, 2022).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…aegypti was prevailed over Ae. albopictus in this urban area and was associated with places with moderate construction activity (Martín et al, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies in this area have shown that Ae. albopictus presents low abundance in urban environments, such as the cities of Eldorado and Puerto Iguazú (Misiones) (Lizuain et al, 2019; Martín et al, 2022; Schweigmann et al, 2004). To date, records show that this species presents high relative abundance only in the rural village of Colonia Aurora (Misiones) (Lizuain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, vegetation index has a positive relationship to egg prediction as well as oviposition activities leading to increased vector activity due to increases in habitat for mosquitoes [ 38 ]. Normalized difference vegetation index (NDVI) and normalized difference water index (NDWI) are the two variable that have been used to determine the vegetation cover and their influence on larval survival, breeding sites, oviposition activity, vector activity, and vector population growth [ 34 , 36 , 38 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aegypti is considered a domestic vector because it is dominant in urban areas, while Ae. Albopictus is mostly found in rural, peri-urban settings and forest areas in tropical, subtropical and temperate regions of the world [ 10 , 36 , 37 , 38 ]. The difference in distribution of these species is related to their behavior based on host preference, blood feeding, preference for vegetation, suitable conditions for resting and ovipositioning [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the connection between the presence of mosquito vectors and Normalized Difference Vegetation Index (NDVI) and Modified Normalized Difference Water Index (MNDWI) [25,26]. In this work, we explore the influence of vegetation spatial distribution measured through NDVI (measure of the density of green on a patch of land), and the presence of surface water measured through MNDWI (measures spectral reflectance patterns) on the presence and abundance of Ae.…”
Section: Environmental Characteristicsmentioning
confidence: 99%